2022
DOI: 10.3389/fpsyt.2022.880747
|View full text |Cite
|
Sign up to set email alerts
|

Measuring catatonia motor behavior with objective instrumentation

Abstract: ObjectiveCatatonia is a neuropsychiatric syndrome, with important psychomotor features, associated with schizophrenia and other psychiatric disorders. The syndrome comprises multiple symptoms including abnormal motor control, behaviors, volition, and autonomic regulation. Catatonia assessment relies on clinical rating scales and clinicians familiar with the catatonia exam. However, objective instrumentation may aid the detection of catatonia. We aimed to investigate the relationship between movement parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
5
1
Order By: Relevance
“…Likewise, previous studies reported an association between activity levels and PS, 27 or catatonia and parkinsonism. 23,33,58 Furthermore, all motor measures assessing PS (except IPAQ) correlated with severity of catatonia and parkinsonism, which is in contrast to a prior report in which neither catatonia nor parkinsonism correlated with a single item measure of PS. 67 However, in line with other reports, PS was strongly associated with negative symptom severity.…”
Section: Multimodal Assessment Of Psychomotor Slowingcontrasting
confidence: 95%
See 1 more Smart Citation
“…Likewise, previous studies reported an association between activity levels and PS, 27 or catatonia and parkinsonism. 23,33,58 Furthermore, all motor measures assessing PS (except IPAQ) correlated with severity of catatonia and parkinsonism, which is in contrast to a prior report in which neither catatonia nor parkinsonism correlated with a single item measure of PS. 67 However, in line with other reports, PS was strongly associated with negative symptom severity.…”
Section: Multimodal Assessment Of Psychomotor Slowingcontrasting
confidence: 95%
“…These findings corroborate prior studies linking lower activity levels to slower processing speed, catatonia, parkinsonism, negative symptoms, and to deteriorating courses in schizophrenia spectrum disord ers. 23,25,27,[30][31][32][33][56][57][58] However, no prior study compared activity levels between psychosis patients with PS and patients without PS. The current report suggests that activity levels measured by actigraphy might be a good marker to identify PS.…”
Section: Multimodal Assessment Of Psychomotor Slowingmentioning
confidence: 99%
“…Then, from adolescence onwards, psychomotor signs may be neglected during phases of subacute manifestations and overshadowed by affective symptoms, prompting diagnoses of mood disorders. Finally, such manifestations may be difficult to perceive due to our fragmented knowledge of catatonia in terms of its definition and clinical description, which varies according to age, severity, and underlying mental disorder (77)(78)(79).…”
Section: Discussionmentioning
confidence: 99%
“…We also enrolled patients with a score of 22 points on the Bush Francis Catatonia Rating Scale. [ 5 ] The patient was diagnosed as having the following conditions: unspecified catatonia; TS. In accordance with the 2021 UK Guidelines for Catatonia, [ 6 ] we prescribed esazolam injections (2 mg twice daily) to relieve the symptoms of catatonia.…”
Section: Case Reportmentioning
confidence: 99%